2020
DOI: 10.1002/rrq.352
|View full text |Cite
|
Sign up to set email alerts
|

How the Science of Reading Informs 21st‐Century Education

Abstract: The science of reading should be informed by an evolving evidence base built on the scientific method. Decades of basic research and randomized controlled trials of interventions and instructional routines have formed a substantial evidence base to guide best practices in reading instruction, reading intervention, and the early identification of at‐risk readers. The recent resurfacing of questions about what constitutes the science of reading is leading to misinformation in the public space that may be viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 150 publications
3
79
0
Order By: Relevance
“…Studies had an experimental or quasi experimental design and included teacher preparation targeting foundational literacy skills. Experimental or quasi experimental designs support stronger causal cred ibility for effective preparation programs (Petscher et al, 2020).…”
Section: Selection Proceduresmentioning
confidence: 99%
“…Studies had an experimental or quasi experimental design and included teacher preparation targeting foundational literacy skills. Experimental or quasi experimental designs support stronger causal cred ibility for effective preparation programs (Petscher et al, 2020).…”
Section: Selection Proceduresmentioning
confidence: 99%
“…Researchers across paradigms must engage in investigations that view literacy and the teaching of reading as a critical sociocultural practice, using a variety of research methods to demonstrate not only what works but also when, why, for whom, and under what circumstances. Quantitative, qualitative, and mixed‐methods designs are necessary to explore these questions (Kamil, Afflerbach, Pearson, & Moje, 2011; Petscher et al, 2020), and given our nation’s large, diverse, multicultural composition, such a multifaceted approach is critical.…”
Section: Our Recommendationmentioning
confidence: 99%
“…As a result, the outcomes of the SOR have influenced multiple areas within education, including research supported by the federal government, the pedagogy of reading, and expectations of teachers and students (Moats, 2007, 2009; Seidenberg, 2013). Scholars have demonstrated that phonemic awareness, phonics, word recognition, decoding, fluency, vocabulary, and comprehension strategies are necessary components for students to acquire to accurately read and understand text (Armbruster, Lehr, & Osborn, 2001; Castles, Rastle, & Nation, 2018; Petscher et al, 2020, this issue; Snow, Burns, & Griffin, 1998; Snow, Griffin, & Burns, 2005; Snowling & Hulme, 2005). Under the influence of the SOR, experimental and quasi‐experimental research is valued as scientific, whereas other types of research (e.g., descriptive, qualitative) are often dismissed as lacking rigor and evidence (Coburn, Pearson, & Woulfin, 2011; Coles, 2003; Shelton, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, better distinguishing between the SOR knowledge base and SOR instructional practices would offer needed precision in scaling effective reading practices. Solari et al (2020) suggested that the gap between the SOR knowledge base and the application of that knowledge base in classrooms can be bridged through translational science, comprising researchers and education stakeholders who cover a range of skills and areas of expertise (Petscher et al, 2020). Translational science teams would continue to generate initial findings through efficacy trails, conducted under ideal conditions, and increasingly examine outcomes in larger effectiveness trials conducted under routine conditions and in population trials where widespread implementation of evidencebased practices occurs.…”
mentioning
confidence: 99%